THE IMPACT OF FLIPBOOK MEDIA ON THE SELF-AWARENESS AND SELF-MANAGEMENT OF NURSING STUDENTS IN PRACTICAL LEARNING - Innez Karunia Mustikarani; Lut Fika Daru Azmi; Apri Nur Wulandari (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Self-management and self-awareness skills, especially in practical learning, must be owned by students. Flipbook is one of the media that helps students and lecturers in teaching and learning activities. This study aims to determine the impact of Flipbook media on the self-awareness and self-management of nursing students in participating in practical learning.Method: The research design used a quasi-experimental pretest-posttest without a control group. The development of digital modules in the form of flipbooks was based on the use of conventional modules during practical learning. The self-awareness and self-management questionnaires used were adapted from Masi, et.al. (2021). The research sample consisted of 186 respondents who were third-semester students of the Nursing Undergraduate Program, taking the Maternity Nursing course, participating in the practical learning process, and completing the pre- and post-test questionnaires. The study was conducted in September 2025 at nursing campus in Semarang. Data were analyzed using the Wilcoxon Signed-ranked test.Results: The results showed that Flipbook media had no effect on nursing students' self-awareness in participating in practical learning (p=0.180 (p>0.05)). However, there was an effect of the Flipbook media on the self-management of nursing students in participating in practical learning (p=0.05). Self-awareness scores tended to increase by 4.6 points and self-management scores increase 1.4 points.Conclusion: Flipbook media did not affect the self-awareness of nursing students in participating in practical learning, while there was an effect of Flipbook media on the self-management of nursing students in participating in practical learning.